Utilization of Fly Ash and Bottom Ash as Acid Mine Water Neutralization Media: Pemanfaatan Fly Ash dan Bottom Ash Sebagai Media Netralisasi Air Asam Tambang - Ardiansah A; Tasya; Muh. Azis Albar J (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
Mine acid water is an environmental impact of mining activities. This becomes even more important if the handling of acid mine drainage is not optimal. Fly ash and bottom ash can be used as alternative utilization of industrial waste to neutralize acid mine drainage. The purpose of this study was to determine the optimal composition of fly ash, bottom ash, and alum to neutralize acid mine drainage and the optimal mass ratio of the fly ash and alum mixture to neutralize mine acid water. Based on the results of testing the optimal mass of fly ash is 0.25 g, 0.50 g, 0.75 g, 1 g, 1.25 g, and 1.50 g with a pH of 6.1, 7.5, 7.6, 7.9, 8.2, and 8.3 which are by the Decree of the State Minister for the Environment number 113 of 2003 concerning wastewater quality standards for mining businesses or activities, namely the pH of water at 6-9 mg/l. Experiments for the maximum use of bottom ash were 1.50 g with a pH of 5. Based on the tests, the optimal mass of a mixture of fly ash and alum was 3.15 g and 3.20 g with a pH of 6.2 and 6.5.